2008
DOI: 10.1590/s0034-72992008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Medidas imitanciométricas em crianças com ausência de emissões otoacústicas

Abstract: Consi dering the hypothesis that middle ear changes can impair the recording of otoacoustic emissions, it is possible that absent otoacoustic emissions in infants could be associated with a light tympanometric change. Aim: To study the association between transient otoacoustic emissions and changes in acoustic immittance measurements with 226Hz probe tone in neonates. Methods: Cross-sectional contemporary cohort study. 20 infants with no transient otoacoustic emissions (study group) and 101 infants with transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
3
15
0
8
Order By: Relevance
“…Being so, the reduction of amplitude can predict possible auditory alterations. In the present study, it was observed that the individuals who use earphones present inferior otoacoustic emissions amplitude compared to those who don't use earphones, even though presenting normal hearing degree in the tonal audio metry 2,8,10,12,14,15,17,27 . It is important to highlight that even knowing that the constant use of portable music players can…”
Section: Resultsmentioning
confidence: 51%
“…Being so, the reduction of amplitude can predict possible auditory alterations. In the present study, it was observed that the individuals who use earphones present inferior otoacoustic emissions amplitude compared to those who don't use earphones, even though presenting normal hearing degree in the tonal audio metry 2,8,10,12,14,15,17,27 . It is important to highlight that even knowing that the constant use of portable music players can…”
Section: Resultsmentioning
confidence: 51%
“…Em relação aos achados da imitância acústica, a literatura estudada determina que existem três tipos fundamentais de curvas timpanométricas conforme a afecção encontrada na orelha média. A curva tipo A, encontrada em indivíduos normais, a curva tipo B, encontrada em paciente portador de otite média secretora, ou seja, com líquido na orelha média, e a curva tipo C, encontrada em paciente portador de mau funcionamento tubário 13,14 . A doença do refl uxo gastroesofágico (DRGE) também é considerada como etiologia de perdas auditivas e uma das principais afecções de orelha média.…”
Section:  Resultadosunclassified
“…Both observations confirm the suggestion of impairment of the central auditory system, as the integrity of the middle ear was confirmed during tympanometry. Studies have confirmed that the absence of the acoustic reflex, and the increase of its thresholds or latency without apparent justification, can be due to the superior olivary complex being unable to execute the command to the facial nerve, to contract the stapedius muscle (9) . Cochlear function, in both cases, was compatible with the psychoacoustic evaluation, as demonstrated by the transient evoked otoacoustic emissions and the DP-OAE.…”
Section: Discussionmentioning
confidence: 99%